Prognosis of Cervical Cancer in the Era of Concurrent Chemoradiation from National Database in Korea: A Comparison between Squamous Cell Carcinoma and Adenocarcinoma. - Jung-Yun Lee; Young Tae Kim; Sunghoon Kim; Boram Lee; Myong Cheol Lim; Jae-Weon Kim; Young-Joo Won (PLoS ONE)
In 1999, the National Cancer Institute issued a clinical advisory strongly touting the advantage of cisplatin-based chemoradiation (CCRT) for cervical cancer patients requiring radiation for their treatment. This study aimed to compare survival outcomes of cervical squamous cell carcinoma and adenocarcinoma before and after the advent of CCRT. Data were obtained from the Korea National Cancer Incidence Database for patients who were diagnosed with cervical cancers between 1993 and 2012. We compared survival according to histologic subtypes in cervical cancer patients diagnosed before (1993-1997), during (1998-2002), and after (2003-2012) the introduction of CCRT. A total of 80,766 patients were identified, including 64,531 (79.9%) women with squamous cell carcinomas and 7,265 (9.0%) with adenocarcinoma. With the introduction of CCRT, survival trends gradually increased in patients of both histologic subtypes with regional tumors. However, survival was significantly higher in squamous cell carcinoma than in adenocarcinoma patients regardless of treatment modalities (surgery alone, P < 0.001; surgery followed by CCRT, P < 0.001; or primary CCRT, P = 0.003). Multivariate analysis showed that adenocarcinoma was an independent negative prognostic factor for survival regardless of the time period (before CCRT, hazard ratio (HR) = 1.49; 95% confidence interval (CI), 1.37-1.62; after introduction of CCRT, HR = 1.40; 95% CI, 1.30-1.50). Although the survival of adenocarcinoma has improved after the introduction of CCRT, adenocarcinoma is still associated with worse overall survival compared to squamous cell carcinoma in the era of CCRT.